2008
DOI: 10.1111/j.1365-2036.2008.03837.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: adverse event reports for oral sodium phosphate and polyethylene glycol

Abstract: SUMMARY BackgroundScreening colonoscopy exposes healthy patients to the risk of serious adverse events associated with bowel preparation. Randomized controlled trials are not an effective method for evaluating this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 78 publications
1
78
0
1
Order By: Relevance
“…These encompass solely cathartic bowel preparation with agents used traditionally to prepare bowel for colonoscopy such as polyethylene glycol or sodium phosphate [1,2]. Full cathartic bowel preparation is associated with significant side-effects, including diarrhoea, abdominal pain and disruption to activities of daily living [3,4], and in extreme cases even death [5]. Previous studies have shown that patients often regard such bowel preparation for bowel investigation as the most burdensome part of the process [6,7].…”
mentioning
confidence: 99%
“…These encompass solely cathartic bowel preparation with agents used traditionally to prepare bowel for colonoscopy such as polyethylene glycol or sodium phosphate [1,2]. Full cathartic bowel preparation is associated with significant side-effects, including diarrhoea, abdominal pain and disruption to activities of daily living [3,4], and in extreme cases even death [5]. Previous studies have shown that patients often regard such bowel preparation for bowel investigation as the most burdensome part of the process [6,7].…”
mentioning
confidence: 99%
“…NaP is a saline laxative administered in two doses of 45 mL diluted in 250 mL water each. Due to its mechanism of action, safety precautions should be taken with patients with a history of or risk of developing renal dysfunction [13] . Many clinical studies have attempted to determine which of these preparations provides better results in terms of colon cleansing, adherence and safety.…”
Section: What Is the Best Agent For Bowel Preparation?mentioning
confidence: 99%
“…In the 90's began to use the sodium phosphate solution (21,22). Sodium phosphate is a saline laxative, which has the advantage of small volume required (2 vials of 45 mL) to achieve a proper colon cleansing, be as effective as and better tolerated by patients than PEG solution (23).…”
Section: Osmotic Solutions Hyperosmolarmentioning
confidence: 99%